Influence of vacuum carburizing treatment on fatigue crack growth characteristic in DSG2 - K. Nambu; N. Egami (Fracture and Structural Integrity)
The aim of this research is to clarify the influence of vacuum carburizing on the fatigue-crack progress characteristics of DSG2 steel. The test specimen tempering material (QT material) and vacuum carburizing material (VC material) has been used. The fatigue-crack progress was examined by subjecting the samples to four-point bending. The loading-capacity fixed experiment was done using a maximum load of Pmax = 4000– 7000 N. The ΔK fixed experiment was done using a load of ΔK = 18–36 MPa√m. The crack progress speed of VC material fell, after the high crack progress speed was shown, and after it showed the minimum, it showed the tendency to go up again. This is considered to be what is depended on the compressive residual stress given to the carburizing layer. From this, it is thinkable that there is a crack progress depression effect in a carburizing layer. In VC material, a carburizing layer has a crack progress depression effect from a plunger-helix bottom to about 2.6 mm, and it turned out that it is larger than an effective carburizing layer. Moreover, in each ΔK, it was shown that depression effect revelation differs and the crack progress process accompanying it was able to be shown typically.